Flowfield Analysis of a Pneumatic Solenoid Valve - Lin, Sheam-Chyun; Lin, Yu-Ming; Haung, Yu-Song; Yao, Cheng-Liang; Jian, Bo-Syuan (Advances in Technology Innovation, 2018)
Pneumatic solenoid valve has been widely used in the vehicle control systems for meeting the rapid-reaction demand triggered by the dynamic conditions encountered during the driving course of vehicle. For ensuring the safety of human being, the reliable and effective solenoid valve is in great demand to shorten the reaction time and thus becomes the topic of this research. This numerical study chooses a commercial 3/2-way solenoid valve as the reference valve for analysing its performance. At first, CFD software Fluent is adopted to simulate the flow field associated with the valve configuration. Then, the comprehensive flow visualization is implemented to identify the locations of adverse flow patterns. Accordingly, it is found that a high-pressure region exists in the zone between the nozzle exit and the top of iron core. Thereafter, the nozzle diameter and the distance between nozzle and spool are identified as the important design parameters for improving the pressure response characteristics of valve. In conclusion, this work establishes a rigorous and systematic CFD scheme to evaluate the performance of pneumatic solenoid valve.